MODELING THE LEVEL OF HARMONIC DISTURBANCES IN ELECTRICAL NETWORKS - TEPTIA, VIRA; OSTRA, NATAL; MALOGULKO, JULIYA; SIKORSKA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The aim of the work is to present modern methods of modeling the level of harmonic distortions and regulatory documentation regulating the permissible levels of harmonic distortions in power networks. One of the main obstacles to the spread of solutions for limiting harmonic distortions was the lack of software products available to a wide range of specialists, which would significantly simplify and speed up the production of relevant calculations and technical solutions. The main research method is practical modeling of the level of harmonic distortions using the Schaffner PQS software package. The evaluation of the obtained results is in accordance with the standards of the IEEE 519-2014 standard. In addition, in order to improve the reception of information, its graphical presentation is proposed. The main results of the research are the implementation of new methods of modeling power networks and obtaining technical solutions in accordance with the IEEE 519-2014 standard. There are also graphic materials available illustrating the impact of harmonic distortions on individual elements of real power networks. This material opens up new possibilities in modeling power networks and assessing the impact of nonlinear receivers on these networks. The use of modern software allows for a significant reduction in the time of performing complex calculations. The availability of ready-made solutions for limiting harmonic distortions in software facilitates the process of creating technical solutions that meet the requirements of the IEEE 519-2014 standard. The use of the tools presented in the work will improve the quality of technical solutions, significantly increase the reliability of electrical systems, reduce electrical energy losses, and increase the efficiency of both design engineers and technical specialists involved in operation.